A Special Thanks to Distinguished Supporters - Ashley A Humphrey (International Journal of Nuclear Security, 2022)
Rhonda Evans, Head of Program Development at World Institute for Nuclear Security (WINS), and Oum Keltoum Hakam, Education Officer at International Atomic Energy Agency (IAEA), have been key supporters of this special issue from the beginning. Along with Danielle Dahlstrom, they both started out as guest editors. They supplied a list of reviewers for this issue and bolstered its importance to some of the most notable professionals in the sector. Despite not having to do any of the editorial work in the journal (thanks to timing, professional responsibilities, and the pandemic), their contribution and continued support deserves a special thanks.